Handbook of research on social interaction technologies and collaboration software : concepts and trends - Dumova, Tatyana, 1962-; Fiordo, Richard, 1945- (Information Science Reference, 2010)
"This book explores the origin, structure, purpose, and function of socially interactive technologies known as social software"--Provided by publisher.